ANALISIS STRATEGI PEMASARAN PADA TOKO WULAN SHOP DI KOTA PAYAKUMBUH DALAM MENINGKATKAN PENDAPATAN DILIHAT DARI PERSPEKTIF MANAJEMEN BISNIS SYARIAH - Nurfilza Inara; Tartila Devy (CV. Adiba Aisha Amira, 2025)
This research is motivated by Sales Strategy in Increasing Revenue. By raising the problem, namely: How is the sales strategy at Wulan Shop in Payakumbuh City to increase revenue seen from the perspective of Sharia Business Management. The purpose of this study is to determine how the sales strategy to increase revenue is seen from the perspective of Sharia business management in the fields of products, pricing, distribution and promotion. The type of research used is descriptive qualitative research. The research methods used in data collection are observation, interviews, and documentation. The data sources used are primary data sources and secondary data sources. Furthermore, data analysis in this study was carried out in three ways, namely data reduction, data presentation, and drawing conclusions. This research was conducted precisely in Koto Baru Village, Payakumbuh Timur District, Payakumbuh City. The results of this study indicate that in increasing its income, Wulan Shop uses a marketing mix strategy consisting of 4p, namely Products (products) consisting of tops, jeans, skirts, gamis, children's clothes, hijab, and so on. Prices (prices) range from Rp. 25,000 - Rp. 350,000. The place is located in Koto Baru Village, Payakumbuh Timur District, Payakumbuh City, and Promotion (promotion) promotional techniques carried out Personal selling, advertising and direct marketing. With several obstacles that occur including, limited product availability, in one model only 2-3 items are available, this can be done by adding variants to each existing product item. The increasing number of competitors offering cheaper prices in online stores, with this can reactivate e- commerce platforms such as TikTok and Shopee. The shop space is not too large, this requires shop expansion but is constrained by quite large capital. With the implementation of this strategy, it is able to increase income by attracting consumer buying interest by paying attention to improving the quality of the products sold, the prices offered, a strategic and comfortable place, and good service by the Wulan Shop in accordance with the values of Sharia business management